Biological treatment technologies for dairy waste water - G. NAGARAJU,; R. SRIKANTH, (International Journal of Pharma and Bio Sciences, 2018)
The developing countries like India have large human population. The population demanded large nutrient food production. To meet the demand of nutrient food products, so many industries are established. In that, dairy industry is most important. Development is directly proportional to environment impact, based on industrial ecology rules, that is Input is equals to output and waste generation. The development of dairy industry creates impact on environment and it pollutes soil, water and air.The effluent water degrades quality of fresh water and affected the organism living in it. The dairy effluent water mainly contaminated the surface water bodies. The dairy wastewater was rich in organic matter and slightly alkaline nature. The effluent water is characterised by biochemical oxygen demand, biological oxygen demand, fats, lactose, high temperature, nutrients, organic matter and inorganic matter.The effluent water, if discharged without treatment, the water bodies are get polluted. Dairy wastewater treatment system should be installed for the protection of the environment health and for the ecological balance. These waters required treatment by primary treatment along with secondary advanced techniques. The objective of the present paper is to give a detailed note on secondary advanced techniques (biological treatment methods) of dairy wastewater treatment methods.